Digitalisasi Strategi Gereja dalam Menjangkau Generasi Z di Era Digital Natives - Vandiano, Vardik (Dekonstruksi, 2026)
ABSTRACT The main challenge faced by churches in the 21st century is the declining presence of young people, particularly Generation Z, within conservative congregations. This situation has created intergenerational gaps and threatens the sustainability of church regeneration. This study aims to examine strategies for engaging Generation Z through the use of digital media, considering that this generation is recognized as digital natives who have been immersed in technology since birth. The research employs a literature review and secondary data analysis from the Bilangan Research Center regarding the digital behavior of Indonesian youth. The findings indicate that internet-based media such as YouTube, Instagram, Facebook, and live streaming platforms hold significant potential as effective tools to reach and engage Generation Z in church life. Churches that are creative, contextual, and digital-friendly are more likely to attract the participation of young people without compromising their faith identity. Thus, the utilization of the digital natives era represents a crucial strategy for churches in addressing the challenges of intergenerational ministry in the modern era. Key Word: Generation Z, Digital Natives, Digital Media, Church, Outreach Strategy ABSTRAK Permasalahan utama gereja di abad XXI adalah semakin berkurangnya kehadiran generasi muda, khususnya Generasi Z, di gereja konservatif. Kondisi ini menimbulkan kesenjangan antargenerasi serta mengancam keberlangsungan regenerasi jemaat. Penelitian ini bertujuan untuk mengkaji strategi penjangkauan Generasi Z melalui pemanfaatan media digital, mengingat generasi ini dikenal sebagai digital natives yang hidup dalam budaya teknologi sejak lahir. Metode penelitian yang digunakan adalah studi literatur dan analisis data sekunder dari Bilangan Research Center mengenai perilaku digital generasi muda di Indonesia. Hasil penelitian menunjukkan bahwa media berbasis internet seperti YouTube, Instagram, Facebook, dan platform live streaming berpotensi besar menjadi sarana efektif dalam menjangkau dan membangun keterlibatan Generasi Z di gereja. Gereja yang kreatif, kontekstual, dan digital-friendly akan lebih mampu menarik partisipasi generasi muda tanpa kehilangan identitas iman. Dengan demikian, pemanfaatan era digital natives merupakan strategi penting bagi gereja dalam menjawab tantangan pelayanan lintas generasi di era modern. Kata Kunci: Generasi Z; Digital Natives; Media Digital; Gereja; Strategi Penjangkauan